MARGINAL REGION MATHEMATICS TEACHERS' PERCEPTION OF USING ICT MEDIA - Trisna Roy Pradipta; Krisna Satrio Perbowo; Afifah Nafis; Asih Miatun; Sue Johnston-Wilder (IKIP Siliwangi and I-MES, 2021)
The article presents a marginal region mathematics teachers' perception of ICT as learning media and the type of ICT media used in mathematics classrooms. A survey was designed including two domains: the usability and the importance of ICT. A questionnaire was administered to 84 mathematics teachers in marginal regions. The respondents were chosen conveniently based on their accessibility and availability. About 50% of marginal region mathematics teachers do not use ICT in teaching. The most common media used is Microsoft Office software to present teaching materials from internet or digital sources. Using the Rasch model, the data show that mathematics teachers' perception of the usage and importance of ICT as a media of mathematics learning can be categorized as 'medium' level. Mathematics teachers in the marginal regions consider ICT as mathematics learning media to be fairly important.